Alat Permainan Edukatif dalam Menanamkan Nilai Agama dan Moral Anak Usia Dini - Al Mubarok, Ahmad Aly Syukron Aziz (PIAUD Universitas Islam Negeri Sunan Kudus, 2021)
EDUCATIONAL PLAY TOOLS IN INSTILLING RELIGIOUS AND MORAL VALUES IN EARLY CHILDHOOD. This research was conducted to provide support for improving educational game tools in instilling religious and moral values. This research method uses Classroom Action Research (CAR) which aims to instill religious and moral values at the early childhood level. This research was conducted at an early childhood education institution, namely RA. Al Musthofa Bangsal. The results of the research through observation from cycles I and II experienced classical learning completeness, namely in the first cycle of meeting 1 the average score of children was 52 completeness 25%. Meeting 2 the average score of the child was 61 completeness 42%. Meeting 3 the mean score of children is 63 completeness 50%. cycle II meeting 1 the average value of the child 67 completeness 58%. Meeting 2 the mean score of children 75 completeness 75%. While meeting 3 the average score of children is 88 completeness 91% means very well developed.